Corporate Governance Ownership Structure and Firm Performance: Evidence from Commercial Banks - Hamid Ullah; Hussain, Amir; Obaid, Zia; Khattak, Benazir Naseem; Ismail, Muhammad (The Journal of Humanities & Social Sciences, 2024)
This study examines the impact of corporate governance and risk management processes on the firm performance. The data has been taken from 23 leading commercial banks in Pakistan from 2010 to 2017. The performance, ownership, governance, and credit risk variables are taken to measure the firm performance. The multiple regression results show that board size, Audit committee independence, director ownership, institutional ownership, foreign ownership, associate ownership, and NPL are positively associated with Return on Equity (ROE), while block holding, capital adequacy ratio, and board independence are negatively correlated with the ROE. Further, the board size, audit committee independence, director ownership, associate ownership, board independence, and NPL have a positive association with the Earning per Share (EPS), and the institutional ownership, foreign ownership, block holding, and capital adequacy ratio have a negative association. Lastly, the audit committee independence, foreign ownership, associate ownership, and capital adequacy ratio are related positively to Return on Assets (ROA), while the rest of the variables like board size, director ownership, institutional ownership, block holding, board independence, and NPL are negatively correlated.